Moenkhausia restricta, a new species from the upper Rio Negro, Amazon basin, northwestern Brazil (Characiformes: Characidae) - Soares, Nathália C. [UNESP]; Benine, Ricardo C. [UNESP] (Magnolia Press, 2019)
A new shallow-bodied species of Moenkhausia is described from the upper Rio Negro, Amazon basin, Brazil. The new species is diagnosed from all congeners by the combination of a body depth not surpassing 33% in SL in adult specimens, seven scale rows between dorsal-fin origin and lateral line, five scale rows between pelvic-fin insertion and lateral line, a single conspicuous vertically elongated humeral blotch, and a conspicuous caudal peduncle blotch extending to the distal margin of the median caudal-fin rays. The new species was collected together with Jupiaba zonata, with which it shares a very similar color pattern. The similarity between these two taxa is interpreted as an additional case of Batesian mimicry between Moenkhausia and Jupiaba.
Keywords: Batesian mimicry; Jupiaba; Pelvic spine; São Gabriel da Cachoeira